Electronic Student Worksheet Based on Problem Based Learning to Improve Critical Thinking of Elementary School Students - Tri Santi; Een Yayah Haenilah; Fatkhur Rohman; Rangga Firdaus (Universitas Pendidikan Ganesha, 2024)
Learning that relies solely on printed textbooks without the application of active learning models can hinder the development of students' abilities, including critical thinking skills. Students become less engaged and have difficulty connecting the material to real-life situations. This study aims to develop a Problem-Based Learning (PBL)-based Electronic Student Worksheet (ESW) and analyze its effectiveness in improving the critical thinking skills of elementary school students. This research is a type of research and development using the Plomp model. The study involved a sample of 53 students divided into two groups: the experimental group, which used the PBL-based ESW, and the control group, which used printed textbooks from the Ministry of Education and Culture (Kemdikbud). Data collection techniques included observation, interviews, documentation, questionnaires, and tests. Data were analyzed using an independent sample t-test, N-Gain, and effect size. The t-test results showed a Sig. 2-tailed value of 0.038 (<0.05), indicating a significant difference between the two groups. The average N-Gain of the experimental class was 0.5779 and the control class was 0.3879, both within the moderate category. The effect size value of 0.587 falls into the large effect category. These results indicate that the application of the PBL-based ESW has a positive and significant impact on improving students' critical thinking skills. Overall, the PBL-based ESW has been proven to be effective in elementary school learning.